Co-infecções por HIV/AIDS, Treponema pallidum e Hepatites B e C entre usuários de um centro de testagem e aconselhamento - Neves, Andréa Carneiro de Menezes (2011)
In Sao Jose do Rio Preto-SP, the current data sum up 3,771 cases of AIDS, with a mortality rate of 1,841. The municipality of Sao Jose do Rio Preto ranks fifth in the number of AIDS cases in the state. Material and method: A retrospective study has been conducted from January 2005 to December 2009. All the HIV-1 seropositive individuals attended by the Testing and Counseling Center were enrolled in the study. Demographic data, epidemiological and clinical data have been analysed: gender, age group, schooling, marital status and co-infection with hepatitis B and C and syphilis. Results: The results showed that the study population was predominately composed of men (74.1%). Men exceed women by 3 to 1. The most frequently age group (70.07%) was between 26-45 years, and 48% of individuals are associated with the category ranging from 8-11 years of schooling. Regarding the single marital status category 60.74% are associated to the subpopulation vulnerable variable, 30.6% and 30.43% of the general subpopulation and chemotherapy dependents, respectively, are associated with couple marital status category. The co-positivity was as follows: HBsAg/HIV, 3.47%; anti-HBc/HIV, 27.2%; and HCV/HIV, 8.39%. The syphilis/HIV screening test was positive in 12.2 %, and the treponema test confirmed 52% of the cases. Conclusion: Co-infections are associated with behavioral factor. These require preventive measures aiming at to reduce the risk and assuring safer sexual practices. Counseling, laboratory testing and distribution of health kits should be incorporated into health services, thus being available to population.